Impact of elective neck dissection on the outcome of oral squamous cell carcinomas arising in the maxillary alveolus and hard palate. (28th November 2015) - Givi, Babak; Eskander, Antoine; Awad, Mahmoud I.; Kong, Qin; Montero, Pablo H.; Palmer, Frank L.; Xu, Wei; De Almeida, John R.; Lee, Nancy; O'Sullivan, Brian; Irish, Jonathan C.; Gilbert, Ralph; et al.
Abstract: Background: Whether elective lymph neck dissection (ELND) is associated with improved survival in oral squamous cell carcinomas (SCC) of the maxillary alveolus/hard palate is not known. Methods: One hundred ninety‐nine patients presenting de novo and receiving treatment for clinically node negative SCC of the maxillary alveolus/hard palate at 2 cancer centers between 1985 and 2011 were analyzed. Results: Forty‐two patients (21%) received ELND. Occult nodal metastases were present in 29% of the dissected necks. The ELND group had more T3 to T4 status tumors (62% vs 34%; p < .001) and positive‐margin resections (59% vs 38%; p = .019). Patients undergoing ELND experienced lower rates of neck recurrence (6% vs 21%; p = .031), superior 5‐year recurrence‐free survival (68% vs 45%; p = .026), and overall survival (86% vs 62%; p = .043). ELND was associated with a 2‐fold decrease in risk of recurrence in multivariable analysis. Conclusion: ELND was associated with lower rates of recurrence and improved survival in SCC of the maxillary alveolus/hard palate. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E1688–E1694, 2016